2016
DOI: 10.1080/08946566.2016.1260083
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among elder abuse victims in rural Malaysia: A two-year population-based descriptive study

Abstract: Our study aims at describing mortality among reported elder abuse experiences in rural Malaysia. This is a population-based cohort study with a multistage cluster sampling method. Older adults in Kuala Pilah (n = 1,927) were interviewed from November 2013 to May 2014. Mortality was traced after 2 years using the National Registration Department database. Overall, 139 (7.2%) respondents died. Fifteen (9.6%) abuse victims died compared to 124 (7.0%) not abused. Mortality was highest with financial abuse (13%), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Worldwide prevalence of EAN was estimated at 3.2% to 27.5% [3]. In Malaysia, one study reported a 12-month prevalence of 9.6% among urban elders [4] while another reported a lifetime prevalence of 8.1% among those in the rural area [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Worldwide prevalence of EAN was estimated at 3.2% to 27.5% [3]. In Malaysia, one study reported a 12-month prevalence of 9.6% among urban elders [4] while another reported a lifetime prevalence of 8.1% among those in the rural area [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Elder abuse and neglect is a significant public health and social problem that has been shown to affect the morbidity and mortality of older persons. [1][2][3] Malaysia is no exception to this phenomenon, and with an imminently aging population comes its share of problems, including elder abuse. Local studies have estimated the prevalence of elder abuse to be 4.5%-9.7%.…”
Section: Introductionmentioning
confidence: 99%
“…A previous research published in the Journal of the American Medical Association mentioned that one in every 10 older adults were engaged in different kind of abuses such as physical, mental, inancial, sexual, and neglectful (Moracco and Cole, 2009) . In Malaysia, the Prevent Elder Abuse and NegleCt InitiativE (PEACE) reported that the lifetime prevalence of elder abuse was 8.1% in the rural area (Yunus et al, 2017).…”
Section: Introductionmentioning
confidence: 99%